2015
DOI: 10.1007/s11107-015-0529-8
|View full text |Cite
|
Sign up to set email alerts
|

Three-port circulators with low symmetry based on photonic crystals and magneto-optical resonators

Abstract: Three-port circulators based on magneto-optical resonators in 2D photonic crystals with low symmetry are investigated. We consider different geometries of the circulators in photonic crystals with triangular and square unit cells. All of the three-ports possess only one specific element of symmetry named antiplane of symmetry. The theoretical part of our paper concerns scattering matrix analysis for different regimes of circulation. In particular, we define the scattering matrices of ideal circulator and a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The theory of stripline and waveguide microwave circulators is well developed [2]. Circulators of different types for optical systems are also described in literature (see, for example, [3,4]). The main function of circulators is protection of a source of signal from unwanted reflections in the circuit, directing the reflected signal to the decoupled port where a matched load is connected.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of stripline and waveguide microwave circulators is well developed [2]. Circulators of different types for optical systems are also described in literature (see, for example, [3,4]). The main function of circulators is protection of a source of signal from unwanted reflections in the circuit, directing the reflected signal to the decoupled port where a matched load is connected.…”
Section: Introductionmentioning
confidence: 99%
“…Different genres of circulators based on PhC technology are renowned. Among them, traditional three-port Y-circulators with a triangular lattice; W and T circulators with a square lattice are familiar and have been reported [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Dmitriev et al reported a W-shape three-port circulator, which does not possess a rotational symmetry [15]. In 2015, the same authors reported a low symmetry three-port circulator based on magneto optic resonators, and also the different geometries of circulators and their scattering matrix [20].…”
Section: Introductionmentioning
confidence: 99%
“…1 Optical circulators have been also discussed in literature. 2,[6][7][8] In THz region, one of the promising tendencies is graphene technology which allows one, in particular, to construct nonreciprocal devices. Recently, an interesting idea of an edge-guided graphene circulator was suggested in.…”
Section: Introductionmentioning
confidence: 99%